Contemporary Japanese Architects (Köln : Benedikt Taschen Verlag, 1994)
Ando, Tadao ; Fujii, Hiromi ; Hara, Hiroshi ; Hasegawa, Itsuko ; Ishii, Katsuhiro ; Isozaki, Arata ; Ito, Toyo ; Kurokawa, Kisho ; Maki, Fumikhiko ; Mozuna, Kiko ; Shinohara, Kazuo ; Takamatsu, Shin ; Yamamoto, Riken
Spaans & Italiaans & Portugees
boek
Keywords: Japan